MANAJEMEN PERSEDIAAN BAHAN BAKU ABON IKAN TUNA PADA UKM SOFIE LOCALFOOD DI KOTA PALU - Selfiani, Selfiani; Tomy, John; Hatmi, Wira (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
Sofie Home Industry is a Small-Medium business operating in the agro-industry sector, specializing in the production of shredded fish using tuna as its primary raw material. The objectives of this research were to determine the optimal procurement quantities for raw materials, to establish the required safety stock levels in the production process, and to identify the appropriate time for placing back orders to ensure a smooth supply of raw materials for the shredded tuna business at Sofie Home Industry. The findings of the study revealed that the average Economic Order Quantity (EOQ) for shredded tuna raw materials during January-December 2020 was 104.65 kg, with an average purchase frequency of 8.16 times. The safety stock for raw materials maintained by Sofie's Home Industry was consistently set at 53.92 kg. Additionally, during January-December 2020, the Reorder Point for raw materials at Sofie's Home Industry was established at an average inventory level of 265.65 kg in the freezer. The total cost incurred by Sofie's Home Industry for the supply of tuna raw materials was averagely IDR 64,127.73 per kg.